Left Ventricular Thrombus Formation in a Structurally and Functionally Normal Heart: A Case Report and Literature Review - Nouraldeen Manasrah MD; Anas Abdel-Qader MD; Ali Al Sbihi MD; Sarah Alqasem MD; Lama Tareq Saif MD; Ahmed J. Chaudhary MD; Rana Ismail PhD, MSc; Ramegowda Rajagopal MD, FACP (SAGE Publishing, 2022)
Left ventricular (LV) thrombosis usually occurs as a complication of acute anterior myocardial infarction (MI) and dilated cardiomyopathy. It also occurs in patients with a hypercoagulable state. However, in the setting of normal systolic function, LV thrombi are extremely rare. We present a case of a healthy woman who had LV thrombus despite normal LV systolic function that presented as an acute aortoiliac embolism.